Activation of RANK/RANKL/OPG Pathway Is Involved in the Pathophysiology of Fibrous Dysplasia and Associated With Disease Burden - de Castro, Luis F (J Bone Miner Res, 2018)
Fibrous dysplasia of bone (FD) is a mosaic disease caused by mutations in GNAS. Constitutive activation of the α-subunit of the G(s) stimulatory protein (Gαs) leads to dysregulated proliferation of bone marrow stromal cells (BMSCs), generating expansile lesions of fibrotic tissue and abnormal bone. Local bone remodeling regulation by BMSCs is also altered, and FD tissue is characterized by abundant osteoclast-like cells that may be essential for lesion expansion. Animal models show local expression of RANKL in bone lesions, and treatment with the RANKL neutralizing antibody denosumab decreased lesion expansion rate in a patient with aggressive FD. However, the role of RANKL/osteoprotegerin (OPG) in FD pathophysiology is not yet understood. We measured serum levels of RANKL, OPG, and inactive RANKL-OPG complexes in FD patients of known disease burden and in healthy volunteers (HVs). RANK, RANKL, and Ki67 immunohistochemistry were assessed in FD tissue. Cultured FD and HV BMSCs were stimulated with prostaglandin E(2) (PGE(2)) and 1,25 vitamin D(3) to increase RANKL expression, and media levels of RANKL and OPG were measured. Osteoclastogenic induction by FD or HV BMSCs was assessed in co-cultures with HV peripheral monocytes. FD patients showed a 16-fold increase in serum RANKL compared to HVs. OPG was moderately increased (24%), although RANKL/OPG ratio was 12-fold higher in FD patients than in HVs. These measurements were positively correlated with the skeletal burden score (SBS), a validated marker of overall FD burden. No differences in serum inactive RANKL-OPG complexes were observed. In FD tissue, RANKL+ and Ki67+ fibroblastic cells were observed near RANK+ osteoclasts. High levels of RANKL were released by FD BMSCs cultures, but were undetectable in HV cultures. FD BMSC released less OPG than HV BMSCs. FD, but not HV BMSCs, induced osteoclastogenesis in monocyte co-cultures, which was prevented by denosumab addition. These data are consistent with the role of RANKL as a driver in FD-induced osteoclastogenesis.